2016
DOI: 10.7748/nm.23.1.22.s26
|View full text |Cite
|
Sign up to set email alerts
|

Revalidation and reflective practice

Abstract: From April 2016 nurses must meet the requirements of the new Nursing and Midwifery Council (NMC) revalidation process to maintain their registration. It is their responsibility to ensure they meet all revalidation requirements, but organisations and nurse leaders can support them to do so. Reflection is an important part of revalidation, and nurses are required to submit written reflective accounts and engage in reflective discussion. This article discusses how revalidation encourages a more conscious and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meanwhile, the description of reflection techniques as an effort to improve professionalism using qualitative methods with a phenomenological approach , this study found a model called the model of professional development in nursing (Gustafsson, 2004).An overview of the strengths and weaknesses of the method of reflection in practice and learning (Nursing and Midwifery Board of Australia., 2016). As well as research conducted at Redcliffe Hospital and Cabolturre found reflective practice as a focus group model (Finch, 2016). Another study involved 127 nurses at University Hospital Quebec on evaluating reflective practice on nurses' attitudes (Dube & Ducharme, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the description of reflection techniques as an effort to improve professionalism using qualitative methods with a phenomenological approach , this study found a model called the model of professional development in nursing (Gustafsson, 2004).An overview of the strengths and weaknesses of the method of reflection in practice and learning (Nursing and Midwifery Board of Australia., 2016). As well as research conducted at Redcliffe Hospital and Cabolturre found reflective practice as a focus group model (Finch, 2016). Another study involved 127 nurses at University Hospital Quebec on evaluating reflective practice on nurses' attitudes (Dube & Ducharme, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…RCD is designed to foster a culture of sharing and enhancing knowledge (Gustafsson, 2004). The research, developed by Finch (2016), concludes that engaging in reflective discussions not only helps you to recognize yourself but helps others to recognize your personality, discussions help relationships, foster work enjoyment, and support shared commitment in the organization. In addition, the preparation of discussion participants is the most important factor in the effectiveness of the discussion (Dube & Ducharme, 2014).…”
Section: Discussionmentioning
confidence: 99%